“Digging Deep”: Using the Task Involvement Load Hypothesis to analyse textbooks for vocabulary learning potential - Rachael Ruegg; Cherie Brown (Lingua Pedagogia, 2019)
In the process of vocabulary acquisition, the extent to which tasks require depth of processing, termed ‘task-induced involvement’ by Laufer and Hulstijn (2001), and the potential effects of this on subsequent vocabulary retention, deserve greater attention. Laufer and Hulstijn (2001) claim that when ‘need’, ‘search’ and ‘evaluation’ are required in order to complete a task, learners engage with words more deeply, thus optimizing potential for successful vocabulary retention. This study was designed to ascertain the extent to which tasks, in commonly used reading textbooks and integrated skills course books, induce ‘deep’ involvement with vocabulary, thus facilitating vocabulary retention. Tasks in 10 reading textbooks and 10 integrated skills course books were analysed in terms of the elements identified by Laufer and Hulstijn (2001). The results were then compared between the two types of textbooks in order to determine whether one is more effective than the other for vocabulary retention.  The study found that the frequency of exposure to target vocabulary was insufficient for vocabulary acquisition. It was also found that many of the vocabulary activities investigated required little task-induced involvement, and more specifically, very few productive activities were found. Keywords: task-induced involvement, depth of processing, vocabulary acquisition, vocabulary retention, vocabulary learning